2014
DOI: 10.1063/1.4874941
|View full text |Cite
|
Sign up to set email alerts
|

Iron contamination in cast quasi-single crystalline silicon ingots

Abstract: Iron is an important metallic impurity in crystalline silicon for solar cells and it can significantly influence the minority carrier lifetime. We numerically investigated the transport and distribution characteristics of iron impurity in the directional solidification process for quasi-single crystalline (QSC) silicon ingots, and attempted to reveal the relationship between the distributions of iron concentration and the minority carrier lifetime map. Additionally, the seed preservation time was varied to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Therefore, the paper mainly studies if the recycled seed crystal with typical iron concentration can be reused. For the solidification process with standard crucible and standard feedstock, the iron profile in the recycled seed crystal varies around the value of 1.0 Â 10 15 atoms/cm 3 , as shown in our previous study [4]. However, the profile is not unique and it varies with the change of preservation time.…”
Section: Model Descriptionmentioning
confidence: 84%
See 2 more Smart Citations
“…Therefore, the paper mainly studies if the recycled seed crystal with typical iron concentration can be reused. For the solidification process with standard crucible and standard feedstock, the iron profile in the recycled seed crystal varies around the value of 1.0 Â 10 15 atoms/cm 3 , as shown in our previous study [4]. However, the profile is not unique and it varies with the change of preservation time.…”
Section: Model Descriptionmentioning
confidence: 84%
“…Some studies have been carried out to study the transport and contamination of iron impurity in the casting process for QSC silicon ingots [4][5][6]. The results show that iron contamination is the main factor for the large low lifetime region at the ingot bottom and the total iron concentration in the seed crystal is more than 10 14 atoms=cm 3 after solidification.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…A significant fraction of QM-Si ingots are typically discarded as unusable due to iron contamination from the seed layer and the crucible wall. [10,11,14,15] A PDG process with phosphorus diffusion at 870 °C for 60 min followed by a low temperature anneal (LTA) significantly increased the harmonic minority carrier lifetime of a QM-Si wafers cut directly from the edge of an ingot from 17 to 178 µs.…”
Section: Resultsmentioning
confidence: 99%
“…Many research groups have identified experimentally and numerically that iron contamination is the main cause of the red zone for casting silicon. [14,15] While the iron contamination is also a problem in traditional mc-Si, it is particularly aggravated for seed-assisted silicon casting due to the back diffusion from the seed, [16][17][18] which leads to an extended red zone for the QM-Si.…”
Section: Doi: 101002/aelm201600435mentioning
confidence: 99%